The accumulation of La, Ce and Y by Lemna minor and Lemna gibba in the Keban gallery water, Elazig Turkey - Sasmaz, Merve; Obek, Erdal; Sasmaz, Ahmet (Wiley, 2018)
This study investigated the phytoremediation ability of Lemna minor and Lemna gibba to accumulate lanthanum, cerium and yttrium from gallery water polluted by metals. L. minor and L. gibba were settled in the mining water and adapted to separate reactors. During the experiment, the water and plant samples were daily taken and the temperature, electric conductivity and pH of the water were daily measured in situ. These plants were firstly washed, dried in and then ashed at 300 degrees C for 24 h in an oven. Both water and ashed plant samples were measured by ICP-MS to detect the concentrations of lanthanum (La), cerium (Ce) and yttrium (Y). Although these elements are at low concentrations in gallery water, they were accumulated at the highest levels in L. gibba and in L. minor. This study showed that both plants have high ability to remove lanthanum, cerium and yttrium in gallery water polluted by different elements.
Keywords: accumulation; aquatic plants; cerium; gallery water; lanthanum; yttrium